2005
DOI: 10.1111/j.1460-9568.2005.03962.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury‐induced lesional expression of the repulsive guidance molecule (RGM)

Abstract: The repulsive guidance molecule (RGM) is involved in the formation of the central nervous system (CNS) during development by modulating guidance of growing axons. However, a role of RGM in CNS injury remains to be established. We studied the expression of RGM in the spinal cord of rats with spinal cord injury (SCI). After SCI, RGM+ cells accumulated in lesions and peri-lesional areas. During the first days after SCI, RGM expression was confined to neurons, ballooned neurite fibers/retraction bulbs, smooth musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 34 publications
(57 reference statements)
2
71
0
Order By: Relevance
“…This is certainly not the case with PC12 cells, which express neogenin but not RGMs and do not die under these conditions. Schwab et al (38,39) observed spinal cord injury-induced lesional expression of the RGM. Lesional RGM expression was frequently confined to hypertrophic ␤-APP ϩ and RhoA ϩ neurites/retraction bulbs.…”
Section: Discussionmentioning
confidence: 99%
“…This is certainly not the case with PC12 cells, which express neogenin but not RGMs and do not die under these conditions. Schwab et al (38,39) observed spinal cord injury-induced lesional expression of the RGM. Lesional RGM expression was frequently confined to hypertrophic ␤-APP ϩ and RhoA ϩ neurites/retraction bulbs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been performed to clarify the role of RGMA in the degenerating/non-regenerating processes of CNS injuries: Schwab et al showed that RGM+ cells accumulated in lesioned and peri-lesional areas after spinal cord injury (SCI), and several glial and non-glial cells and tissues (including the mature and maturing scar) showed RGM immunoreactivity [21]. It was also shown in rats after SCI that inhibition of RGM enhanced growth of injured axons, promoted functional recovery [22], and induced synaptic rearrangements of spared axonal projections [23].…”
Section: Introductionmentioning
confidence: 99%
“…In the healthy adult human brain, immunohistochemistry with a pan-RGM antibody revealed that RGM proteins are located on perikarya of some neurons, chorioid plexus, smooth muscle of the vasculature, endothelial cells and on oligodendrocytes and white matter fibre tracts (Schwab et al 2005a). A similar staining pattern was also observed in the rat brain, suggesting that RGM proteins could act in concert with myelin-associated inhibitors Nogo-A, MAG and OMGp to restrict or prevent plasticity of neurites in the adult mammalian CNS (Schwab et al 2005b). This evolutionary conserved expression pattern of RGM proteins provides evidence that RGM proteins are potential inhibitors of neuroregeneration and it was therefore important to analyse their expression in the injured or stroke-damaged human brain.…”
Section: Role Of Repulsive Guidance Molecules In Adult Vertebrate Cnsmentioning
confidence: 64%